2018
DOI: 10.1590/s1413-41522018177756
|View full text |Cite
|
Sign up to set email alerts
|

Caracterização e avaliação de fatores que determinam a remoção de microcistina-LR em carvão ativado granular produzido a partir de diferentes matérias-primas

Abstract: RESUMO As microcistinas (MC), que estão entre as cianotoxinas mais encontradas em florações de cianobactérias, não são eficientemente removidas pelas tecnologias do ciclo completo de tratamento de água. Como barreira adicional para sua remoção, destaca-se o processo de adsorção com carvão ativado granular (CAG). Esta pesquisa comparou a eficiência de remoção de MC-LR por sete CAG produzidos a partir de diferentes matérias-primas, analisando as propriedades das amostras: umidade, teor de cinzas, pH e caracterís… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
1
0
4

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 30 publications
(24 reference statements)
1
1
0
4
Order By: Relevance
“…The only exception was GAC since the highest retention values for the three analytes were obtained by using 0.05 g of the adsorbent. A decrease in the adsorption capacity of the GAC was also observed by Borges et al 36 and Araujo et al 37 The GAC particles were larger than those of the other adsorbents and equivalent to those of XAD-2 (Table 2). However, the irregular shape of the GAC particles led to poor column packing compared to the others.…”
Section: Resultssupporting
confidence: 77%
“…The only exception was GAC since the highest retention values for the three analytes were obtained by using 0.05 g of the adsorbent. A decrease in the adsorption capacity of the GAC was also observed by Borges et al 36 and Araujo et al 37 The GAC particles were larger than those of the other adsorbents and equivalent to those of XAD-2 (Table 2). However, the irregular shape of the GAC particles led to poor column packing compared to the others.…”
Section: Resultssupporting
confidence: 77%
“…De acordo com os coeficientes de correlação (R 2 ) para cada ajuste, a isoterma que melhor representa o processo de adsorção é a de Langmuir, que obteve o valor mais próximo de 1. Resultado contrário aos realizados com o biocarvão do bagaço da laranja para adsorção de ácido acético [25] e corroborado com os experimentos de [26] com biocarvão de cascas de laranja para remoção de contaminantes inorgânicos Zinco (Zn), Alumínio (Al), Cádmio (Cd), Cobre (Cu), Níquel (Ni) e Chumbo (Pb) e do orgânico Etilbenzeno e [27] com carvão ativado granular. Segundo este modelo, estamos partindo dos pressupostos que a adsorção acontece em monocamadas, com sítios ativos do carvão em igual afinidade pelo adsorvato, em que as interferências na adsorção de sítios vizinhos são desprezadas, e uma das características importantes para o presente artigo é que a isoterma de Langmuir indica que a adsorção é reversível [28,18].…”
Section: Isotermas De Adsorçãounclassified
“…Similarly, the nature of functional groups on the carbon surface is determinant in the capacity of trapping MCs [95]. For instance, it was reported that there is strong proton adsorption in the case of the presence of several hydroxyl or phenolic groups under certain pH conditions [95,97,100]. Activated carbon may derive from different materials, namely wood, coal, coconut shells, or peat [75,92,[101][102][103].…”
Section: Filtration and Complexationmentioning
confidence: 99%